Прилог кон идентификување на свети Давид цар и свети Теоктист од бакрорезите на Христофор Жефарович - Nedeski, Viktor (Завод за заштита на спомениците на култура и музеј - Струмица, 2020)
The "Stemmatographia" of one of the first Macedonian revivalists, Hristofor Zhefarovich, is one of the most significant monuments of South Slav culture in the 18th century. This small but rich and luxurious chalcography book featuring the coats of arms and figures of the rulers and saints, written in Church Slavic language with Russian redaction, was not only a template for engravers and iconographers, but had and still has a profound impact on the understanding of the creation of nati ons in the Balkans. It carries multiple messages that have been interpreted to this day, and some of them have been interpreted differently in different national-politi cal contexts and tendencies. Among the portraits of the South Slavic saints in the Stematography of Hris tofor Zhefarovich are the portraits of St. David the King and St. Theoctist. Of particu lar interest in identifying the two mentioned portraits is another Zefarovich's chalco graphy from the same 1741 which was made just months before the publication of his "Stemmatographia". In the image of St. David clearly is identified, the Serbian nobleman Dimitrij Nemanjic, son of Vukan, nephew of Stefan Nemanjic. As a monk David, he is revered as a saint of the Serbian Orthodox Church and founder of the Davidovica monastery in southwestern Serbia. Paisius of Hilendar baselessly linked the image of "Saint Da vid the King of Bulgaria" with David - brother of Samuel. The character of the monk Theoctist, on the other hand, is identified as King Stefan Dragutin Nemanjic, son of Stefan Uros I, and nephew of Stefan the First-Crow ned. At the end of his life, Dragutin became a monk with the monastic name Theo ctist. In the character of Theoctist, Paisius again baselessly recognized the Bulgarian ruler, King Trivelius or Tervel.